Influence of the photodiode spectral sensitivity on the temperature estimation by sxr using thin filtering foils in Uragan-3M - Dreval, M.B.; Turianska, O.V.; Pahur, A.S. (Вопросы атомной науки и техники, 2020)
Soft X-ray (SXRƚ diagnostics is routinely used in Uragan-3M (U-3M) torsatron. One of the SXR diagnostic applications is based on the plasma temperature estimation. The ratio of SXR signals passed through two different foils depends only on the plasma temperature and can be used for its estimation. An influence of spectral sensitivity of the photodiode on the two foils temperature estimations technique is considered in present work numerically. The influence is negligible in the case of the flat sensitivity in the energy range 5…500 eV in the case of thin 1.5 ⁄ 2.25 μm Al foils. In the opposite case of very low spectral sensitivity in 5…500 eV range and its increase at the 1 keV range the signals ratio can be very high. This result can explain high signals ratio experimentally observed in Uragan-3M stellarator, where photodiodes with unknown spectral sensitivity were used.